2022
DOI: 10.1128/spectrum.00580-22
|View full text |Cite
|
Sign up to set email alerts
|

A tRNA-Acetylating Toxin and Detoxifying Enzyme in Mycobacterium tuberculosis

Abstract: The global rise in antibiotic-resistant tuberculosis has prompted an urgent search for new drugs. Toxin-antitoxin (TA) systems allow bacteria to adapt rapidly to environmental changes, and Mycobacterium tuberculosis encodes more TA systems than any known pathogen.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Both types of strains had growth defects that were proportional to the level of depletion (Figure 1), confirming that pth is required for normal growth of Mtb . Due to the technical ease of validating pth knockdown levels and our use of the tightly-regulated transcriptional repression strain in published work [22], we used the CRISPRi Pth depletion strain for subsequent experiments in this work.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both types of strains had growth defects that were proportional to the level of depletion (Figure 1), confirming that pth is required for normal growth of Mtb . Due to the technical ease of validating pth knockdown levels and our use of the tightly-regulated transcriptional repression strain in published work [22], we used the CRISPRi Pth depletion strain for subsequent experiments in this work.…”
Section: Resultsmentioning
confidence: 99%
“…We previously characterized a second function for Pth in Mtb . In addition to its peptidyl tRNA hydrolase activity, Pth is a detoxifying enzyme for a tRNA-acetylating toxin TacT that is part of a newly-identified toxin-antitoxin system [22]. We found that this function does not contribute to pth essentiality in Mtb since TacT was not active during normal laboratory growth conditions and a tacAt knockout strain was equally susceptible to pth depletion by CRISPRi [22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations